An integrated population model of a high‐density coyote population in South Carolina, USA - Heather E. Gaya; Gino J. D'Angelo; Jordan L. Youngmann; Stacey L. Lance; John C. Kilgo (Ecosphere, 2025)
Abstract In the absence of red wolves (Canis rufus), coyote (Canis latrans) populations have expanded across the eastern United States. However, predator populations are particularly difficult to quantify, and it remains unclear if and when eastern coyotes will reach carrying capacity. To assess coyote population trends, we constructed an integrated population model (IPM) using coyote data recorded at the United States Department of Energy's Savannah River Site (SRS), a 78,000‐ha National Environmental Research Park located in South Carolina, United States. Coyote densities averaged 50 coyotes/100 km2 prior to lethal control in 2010 but dropped to 14 coyotes/100 km2 in 2012 after three consecutive years of intensive lethal removal. By 2014, coyote densities stabilized around 44 coyotes/100 km2. These results suggest that coyote populations can decline under sustained intensive control efforts but may rapidly increase when control efforts are ceased. Our results highlight the power of IPMs to estimate population parameters across long time scales when data collection is both spatially and temporally heterogenous. Lethal control efforts for coyotes are prohibitively expensive at a large scale and are unlikely to be a viable long‐term management strategy. Managers should instead focus on setting game species hunting limits that account for coyote presence on the landscape.